2023
DOI: 10.1177/23294965231159306
|View full text |Cite
|
Sign up to set email alerts
|

“I Went There”: How Parent Experience Shapes School Decisions

Abstract: As school choice expands, families face an increasingly arduous decision-making process around school enrollment. Through interviews with a socioeconomically and ethno-racially diverse sample of 60 parents in Dallas, Texas, we illustrate one key way families negotiate this choice landscape. We find that many parents use their own educational experiences as first-stage decision rules for narrowing the types of schools they consider for their children through experience-motivated replication and experience-motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For Black families, conceptions of school quality factor in their children's overall physical, social, and emotional safety (Pattillo, 2015;Posey-Maddox et al, 2021). As Rhodes et al (2023) observed, parents' experiences in schools can shape their choice set construction. For example, the authors found that parents sought to either replicate their positive experiences in certain types of schools or avoid schools where they had negative experiences.…”
Section: Black Parents' Educational Decision-making Processesmentioning
confidence: 98%
See 1 more Smart Citation
“…For Black families, conceptions of school quality factor in their children's overall physical, social, and emotional safety (Pattillo, 2015;Posey-Maddox et al, 2021). As Rhodes et al (2023) observed, parents' experiences in schools can shape their choice set construction. For example, the authors found that parents sought to either replicate their positive experiences in certain types of schools or avoid schools where they had negative experiences.…”
Section: Black Parents' Educational Decision-making Processesmentioning
confidence: 98%
“…For example, the authors found that parents sought to either replicate their positive experiences in certain types of schools or avoid schools where they had negative experiences. Patterns of avoidance and replication were racialized, and Black families most frequently employed avoidance strategies and eliminated schools from their choice sets where they perceived their children would not be adequately served (Rhodes et al, 2023).…”
Section: Grounding Literaturementioning
confidence: 99%